Intra-operative factors responsible for conversion of laparoscopic cholecystectomy to open cholecystectomy in a tertiary care center - Saeed, Anam; Salim, Mohammed; Kachhawa, Devi Singh; Chaudhary, Renuka (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is the gold standard treatment for symptomatic cholelithiasis and has multiple advantages over open approach. With increasing skills and techniques over the years, the contra-indications to laparoscopic cholecystectomy have reduced. Even after careful selection of appropriate candidates for laparoscopic cholecystectomy, it sometimes becomes necessary to convert into an open cholecystectomy to prevent complications. This study was undertaken so as to identify the intra-operative factors necessitating conversion of laparoscopic cholecystectomy to open cholecystectomy. Methods: In this study conducted at S. P. Medical College and P. B. M. Hospital, Bikaner, over a period of 1 year, 100 consecutive patients with symptomatic cholelithiasis, planned for laparoscopic cholecystectomy were included. Laparoscopic cholecystectomy was performed and cases which could not be completed laparoscopically were converted to open cholecystectomy via right subcostal incision. Intra-operative factors necessitating conversion were observed and analyzed. Results: The incidence of conversion was found to be 7%. The most common intra-operative factor for conversion was dense adhesions at the Calot’s triangle (71.43%) followed by obscure anatomy (42.86%). Uncontrolled bleeding and CBD stones also led to conversion. The identification and appearance of CBD and achievement of critical view of safety were significant factors for conversion to open cholecystectomy (p=0.0001). Conclusions: The rate of conversion to open cholecystectomy was 7% which is comparable to similar studies. Conversion is not a failure or complication but actually a safer alternative to ensure completion of the procedure without any real complications of laparoscopic cholecystectomy- biliary or visceral injury, haemorrhage, etc.